Lead and Antimony in Basal Ice From Col du Dome (French Alps) Dated With Radiocarbon: A Record of Pollution During Antiquity. Issue 9 (7th May 2019) - Preunkert, Susanne; McConnell, Joseph R.; Hoffmann, Helene; Legrand, Michel; Wilson, Andrew I.; Eckhardt, Sabine; Stohl, Andreas; Chellman, Nathan J.; Arienzo, Monica M.; Friedrich, Ronny
Abstract: Lead and antimony measurements in basal ice from the Col du Dome glacier document heavy metal pollution in western Europe associated with emissions from mining and smelting operations during European antiquity. Radiocarbon dating of the particulate organic carbon fraction in the ice suggests that the basal ice dates to ~5, 000 ± 600 cal years BP. In agreement with a precisely dated Greenland lead record, the Col du Dome record indicates two periods of significant lead pollution during the Roman period, that is, the last centuries before the Common Era to the second century of the Common Era. Atmospheric modeling and the Col du Dome record consistently show an overall magnitude of the lead perturbation 100 times larger than in the Greenland record. Antimony closely tracked lead, with antimony pollution about 2 orders of magnitude lower, consistent with European peat records. Plain Language Summary: Measurements of radiocarbon on particulate organic matter trapped in ice showed that the deepest ice of the Mont Blanc glacier covers the entire period of antiquity (from 800 BCE to 250 CE). Lead measurements indicated significant metal pollution during the Roman Republican and the Imperial period, that is, during the last centuries before the Common Era to the second century of the Common Era, with much lower levels before and after. We show that the Roman‐era emissions enhanced the natural lead level by at least a factor of 10, which was already significant compared to the modern enhancement by a factor of 100 due to lead emissions related to the use of leaded gasoline. This first ice record of pollution by antimony, another toxic heavy metal, during antiquity showing large Roman‐era increases in parallel with lead, confirms that early mining and smelting activities had environmental implications beyond simply lead contamination. Key Points: Lead and antimony Alpine ice records spanning European antiquity provide evidence of past Roman mining activities Radiocarbon analysis of Col du Dome (Mont Blanc, French Alps) basal glacier ice suggests ice as old as ~5, 000 ± 600 cal years BP Comparison between Greenland and Alpine lead ice records consistently shows the effect of Roman mining in proximity to the Alps